Component Tolerance and Performance of 2-Way Passive Crossovers: Toleransi Komponen dan Kinerja Penyeberang Pasif Dua Arah - Akhmad Ahfas; Adriana Anteng Anggorowati; Dwi Hadidjaja R.S. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Passive 2-way crossover filters play a crucial role in dividing audio signals between woofer and tweeter channels, where their performance is highly dependent on the precision of passive components. Specific Background: Variations in capacitor and inductor values, along with their tolerances, can significantly alter crossover frequency, phase characteristics, and harmonic distortion, yet these effects are not fully quantified in practical implementations. Knowledge Gap: Limited studies provide an integrated empirical–analytical assessment of how component deviations influence frequency response, THD, and impedance stability in real passive 2-way filters. Aims: This study evaluates the influence of component tolerances on crossover frequency accuracy, filter slope behavior, phase stability, and distortion performance. Results: Experimental findings show that ±10–15% component deviations shift crossover frequency by 7.1–8.5%, reduce filter slope by 2.1–3.2 dB/octave, increase THD from 0.8% to 3.2% at 10W, and induce impedance fluctuations that shift the crossover point by an additional 3.2%. Inductors exhibit higher sensitivity (0.72–0.78) than capacitors (0.45–0.52). Novelty: This study provides a combined simulation–measurement analysis linking component tolerance to measurable acoustic deviations. Implications: The results highlight the need for ≤5% tolerance components and pre-assembly verification to ensure stable crossover performance. Highlights: Component tolerances significantly shift crossover frequency and reduce filter accuracy. Inductors have a stronger impact on system performance than capacitors. Using ≤5% tolerance components improves stability, distortion, and overall audio quality. Keywords: Passive Crossover Filter, Component Tolerance, Crossover Frequency Shift, Total Harmonic Distortion, Impedance Stability